Subharmonics with Minimal Periods for Convex Discrete Hamiltonian Systems - Honghua Bin (Abstract and Applied Analysis)
We consider the subharmonics with minimal periods for convex discrete Hamiltonian systems. By using variational methods and dual functional, we obtain that the system has a -periodic solution for each positive integer , and solution of system has minimal period as subquadratic growth both at 0 and infinity.